If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 1 = 5x + -1 Reorder the terms: 1 + X = 5x + -1 Reorder the terms: 1 + X = -1 + 5x Solving 1 + X = -1 + 5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + X = -1 + -1 + 5x Combine like terms: 1 + -1 = 0 0 + X = -1 + -1 + 5x X = -1 + -1 + 5x Combine like terms: -1 + -1 = -2 X = -2 + 5x Simplifying X = -2 + 5x
| 53a-7.9=26a+29 | | 3/5(z-3)-11/5=-4 | | 7+2y=3.4 | | V/10.44-2.8=-4.422 | | X^2-9x^2+18=0 | | -5u+3(u+5)=29 | | Lnx^3/x^6 | | 14.63/9.315 | | 34z+63=-17z+471 | | 2/3(z-2)-11/3=-5 | | 5x+33=98 | | 10-10d=20 | | 2v=21 | | -80+-4x=120+6x | | (x+1)(x-1)=(x+1)(x-2) | | -80x+-4x=120+6x | | 3x-19=-70 | | 23-5=110 | | -(6y+1)-(-5y-8)=0 | | 3x^2-24x+28=0 | | 83overx=7 | | 3h-7=-7 | | -2(x-2)=-4x+14 | | -5-(-5/2) | | 33x-2+12x+2=180 | | -5/2-(-5/4) | | 33x-2+12+2=180 | | -75-11x=46 | | 6v-4=-2(v-2) | | 8/5k-3/2k= | | K/12-1=-3 | | x^3/x^6 |